2017
DOI: 10.15376/biores.12.2.3182-3191
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Flower-like ZnO Nanoparticles in a Cellulose Hydrogel Microreactor

Abstract: *Flower-like zinc oxide (ZnO) nanoparticles were synthesized with sodium hydroxide and zinc acetate in a cellulose hydrogel microreactor (prepared by the inversion method). The samples were characterized by scanning electron microscopy, EDX, x-ray diffractometry, ultravioletvisible diffuse reflection spectroscopy, and nitrogen adsorptiondesorption. The results indicated that ZnO grows in a flower-like shape in the pores of the cellulose hydrogel. The pure hexagonal wurtzite structures have uniform diameters in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 32 publications
1
1
0
Order By: Relevance
“…4B). 74 These results validate the applicability of microfluidic reactors (even in a bioresource form) in the controllable synthesis of flower-like structures, providing new insights for the development of hierarchical ZnO products.…”
Section: Biomaterials Science Reviewsupporting
confidence: 62%
“…4B). 74 These results validate the applicability of microfluidic reactors (even in a bioresource form) in the controllable synthesis of flower-like structures, providing new insights for the development of hierarchical ZnO products.…”
Section: Biomaterials Science Reviewsupporting
confidence: 62%
“…In addition, SIRT5 promotes the acetylation of p65 and the activation of the NF-κB pathway, as well as its downstream cytokines, and enhances the innate inflammatory responses in normal and endotoxin-tolerant macrophages [62]. Numerous studies have shown that pro-inflammatory cytokines, such as IL-1β and TNF-α, are abnormally elevated in NDs [63,64]. In a PD model, mitochondrial sirtuins alleviate inflammation by inhibiting the NF-κB signaling pathway, thus reducing DA neuron damage [62,65,66].…”
Section: Regulation Of Inflammatory Signaling Pathwaysmentioning
confidence: 99%
“…The metal phase in a cellulose metallogel can provide this material with catalytic activity in the reactions of such "chemical" water purification (Figure 3). For example, zinc oxide reveals outstanding photocatalytic performance, making it suitable for degrading complex organic compounds such as dyes and pharmaceuticals [113]. Thus, a ZnO/cellulose composite was synthesized by regenerating a cellulose hydrogel from a NaOH/urea/H 2 O (7:12:81) solution, followed by immersion in an ethanol solution of zinc acetate.…”
Section: Wastewater Treatmentmentioning
confidence: 99%
“…After 180 min, the degradation rate of Rh B using the ZnO/cellulose composite and ZnO without the hydrogel reached 95.2% and 45.2%, respectively. This suggested that the cellulose hydrogel acted as a microreactor, enhancing the catalyst's activity twofold [113].…”
Section: Wastewater Treatmentmentioning
confidence: 99%